BLENDED ONLINE LEARNING: COMBINING THE STRENGTHS OF SYNCHRONOUS AND ASYNCHRONOUS ONLINE LEARNING IN EFL CONTEXT - Cahyani, Ni Made Wahyu Suganti; Suwastini, Ni Komang Arie; Dantes, Gede Rasben; Jayantini, I Gusti Agung Sri Rwa; Susanthi, I Gusti Ayu Agung Dian (Universitas Pendidikan Ganesha, 2021)
The ubiquitous use of digital technology brings the inevitability of online learning and its varying degree of teacher-student interactions, both in synchronous and asynchronous online learning modes. This present study reviews the strength and weaknesses of the two online learning modes to propose the use of blended online learning as the combination that harvests the strengths of asynchronous and synchronous modes of online learning with the opportunity to cover each other's weaknesses. The recent study employed Aveyard's literature review model as a method for gaining a comprehensive understanding of a specific topic using data and arguments from previous studies. Thirty-six articles published in reputable international journals or accredited national journals published in 2015-2020 were used. This review revealed that blended online learning combines the strengths of synchronous and synchronous learning in terms of authentic learning activities, flexibility, access, interaction, development of critical thinking, comprehension, and mastery, and student-centered nature of the learning. However, it still retains challenges in terms of network and connection issues from both online learning modes. This finding implies that blended learning can be the middle-ground to facilitate online learning with benefits from both synchronous and asynchronous online modes by minimizing the students’ exposure to the weaknesses from the two modes.